Optimal waist circumference threshold for diagnosing metabolic syndrome in African people living with HIV infection. - Kim A Nguyen; Nasheeta Peer; Anniza de Villiers; Barbara Mukasa; Tandi E Matsha; Edward J Mills; Andre P Kengne (PLoS ONE)
Background The applicability of the internationally advocated cut-off points of waist circumference (WC) derived from Caucasians to diagnose metabolic syndrome (MS) in HIV-infected Africans is unknown. This study aimed to determine the optimal WC cutoffs for MS diagnosis in HIV-infected people receiving care at public healthcare facilities in the Western Cape Province in South Africa. Methods Data from 748 randomly selected participants (591 women), with a median age of 38 years, were analysed. The Youden's index and the top-left-point approaches were used to determine the optimal cutoffs of WC for predicting ≥2 non-adipose MS components. Results The two approaches generated the same WC cut-off point in women, 92 cm (sensitivity 64%, specificity 64%) but different cut-off points in men: 87 cm (sensitivity 48%, specificity 85%) based on the Younden's index and 83 cm (sensitivity 59%, specificity 74%) by the top-left-point method. The advocated thresholds of 94 cm in men had low sensitivity (30%) but high specificity (92%) whereas 80 cm in women showed low specificity (32%) but high sensitivity (85%) for diagnosing MS in this sample. Most African-specific cut-off points performed well, with 90 cm providing acceptable performance in both men (sensitivity 43%, specificity 88%) and women (sensitivity 66%, specificity 59%). Conclusions This study underlines the sub-optimal performance of internationally recommended WC thresholds for MS diagnosis in HIV-infected Africans, and supports the need to revisit the guidelines on WC criterion in African population across the board. A single threshold of 90 cm for both genders would be a practical suggestion.